Boron(III)‐Catalyzed C2‐Selective C−H Borylation of Heteroarenes. Issue 45 (12th October 2018) - Zhong, Qi; Qin, Shengxiang; Yin, Youzhi; Hu, Jiajun; Zhang, Hua
Abstract: A BF3 ⋅Et2 O‐catalyzed C2‐selective C−H borylation of indoles with bis(pinacolato)diboron was developed to afford indole‐2‐boronic acid pinacol esters. A variety of functional groups were tolerated, and other heteroarenes like pyrrole and benzo[ b ]thiophene were also suitable substrates. An electrophilic substitution mechanism was proposed based on the preliminary mechanistic studies. This novel transformation utilizes simple and cheap BF3 ⋅Et2 O as catalyst and exhibits unusual C2 regioselectivity, providing a significant non‐transition‐metal‐catalyzed C−H borylation and an efficient method towards the synthesis of C2‐functionalized heteroarenes. Abstract : Busy B : A BF3 ⋅Et2 O‐catalyzed C2‐selective C−H borylation of indoles, as well as other heteroarenes, with bis(pinacolato)diboron was developed. An electrophilic substitution mechanism is proposed based on preliminary mechanistic studies. This transformation provides a significant non‐transition‐metal‐catalyzed C−H borylation method for the synthesis of C2‐functionalized heteroarenes.